(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the paper is to evaluate the wear mechanism that occur in the artillery armament main part – gun tube. In order to achieve this purpose, the mechanism of wear has been derived by means of studying the information from literary sources and drawing conclusions. The topicality of the topic is dictated by the constant aspiration of scientists to derive a new theory, reduce the manufacturing resources and increase the wear resistance of the gun tube. The study of the problem led to an assessment of the processes occurring in the gun tube of the artillery system. As a result of the study, it can be pointed that a different theory of the wear mechanism of special purpose machine elements has been established.